Diagnosis of Basic Mathematics Learning Difficulties for Students from Science, Social Studies, and Vocational High School Backgrounds - Netriwati, Netriwati; Mulya, Neni (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
This research aims to explore the specific learning challenges encountered by students in the Mathematics Education Program at UIN Raden Intan Lampung, especially those with educational backgrounds in Science, Social Studies, and Vocational Studies, in the context of mathematics learning. Adopting a qualitative approach, this study employed purposive and Snowball Sampling techniques. It focused on students from classes A and B in the Mathematics Education Program. The findings reveal that students with a Science background tend to struggle with concept comprehension and the application of mathematical problem-solving techniques. Furthermore, a significant factor contributing to learning difficulties, observed in students from Science, Social Studies, and Vocational backgrounds, is a lack of interest in learning. The study concludes that the learning challenges faced by Mathematics Education students are not solely attributable to their educational backgrounds (Science, Social Studies, or Vocational). Instead, a predominant factor is their low level of interest in learning. This suggests the need for diverse learning strategies to enhance interest and understanding of mathematical concepts among students.